A Literacia Digital e as Competências Digitais para a Infoinclusão: por uma inclusão digital e social dos mais idosos - Gil, Henrique (2021)
The aim of this article is to present an overview of the main initiatives of the European Union and the national initiatives concerning the process leading to the submission of proposals related to digital literacy and digital skills as a way to promote the competitiveness of each country. Then we proceed to a critical and reflexive analysis about the concept or concepts underlying what is understood as digital literacy and digital competences through the confrontation of perspectives of various authors. Following this discussion, an approach is done in relation to the problems that arise from being info-included and info-excluded, with a particular focus on older adults, since they represent citizens with the lowest rates of access and use of digital technologies. The finding of the so-called digital divides entails a potential social exclusion with all the inherent consequences. However, it is also discussed the fact that we may be faced with a new digital divide that can be intergenerational or intragenerational because, from the reflection made, the clear notion emerges that digital literacy and associated digital competences are only present if there is a critical attitude and the use and mobilization of digital technologies instead of more functional or instrumental aspects.